Faktor-faktor Yang Mempengaruhi Minat Berwirausaha Siswa SMK di Jakarta - Rifki Saepul Ardiansyah; Corry Yohana; Nadya Fadillah Fidhyallah (Fakultas Ekonomi Universitas Negeri Jakarta, 2021)
This study aims to determine the positive and significant influence between entrepreneurial knowledge and internal locus of control on the intention in entrepreneurship of 11th grade students of SMK Negeri 16 Jakarta. This research was conducted at SMK 16 Jakarta. The research method used is the survey method. The population in this study were all 11th grade students of SMK Negeri 16 Jakarta, totaling 214 students. The sampling technique in this study was proportional random sampling, where the sample used was 143 respondents who were obtained after being processed by the Slovin formula with a standard error of 5%. The data analysis technique used is simple linear regression analysis using IBM SPSS version 22. The results of hypothesis testing indicate that (1) entrepreneurial knowledge has a positive and significant effect on entrepreneurial interest with a coefficient of determination of 35.3% and (2) internal locus of control has a positive and significant effect on entrepreneurship. significant to the interest in entrepreneurship with a coefficient of determination of 12.3%.